Propagation of Impact of the Recent Major Baltic Inflows From the Eastern Gotland Basin to the Gulf of Finland - Liblik, Taavi; Naumann, Michael; Alenius, Pekka; Hansson, Martin; Lips, Urmas; Nausch, Günther; Tuomi, Laura; Wesslander, Karin; Laanemets, Jaan; Viktorsson, Lena (Frontiers in Marine Science, 2018)
Major Baltic Inflows (MBI) have a significant impact on physics, biogeochemistry and marine life in the Baltic Sea. Spreading of the North Sea water from the Danish Straits to the Eastern Gotland Basin has been rigorously studied in recent decades. Investigations of lateral signal propagation using in-situ measurements, which cover the area from the Eastern Gotland Basin to the Gulf of Finland, are missing. Estonian-Swedish-German-Finnish oceanographic data from January 2014 to March 2017 were merged and analyzed to fill the gap. Recent MBIs caused considerable changes in water column properties, and salinity reached the highest values of the last 40–60 years. The arrivals of MBI waters were detected as peaks in the salinity and temperature time-series in the near-bottom layer of the Gotland Deep 4–5 months after the MBI events. Similar peaks were also identified in the Fårö Deep, Northern Deep and Kõpu West (Northern Baltic Proper) with a further delay of 2–3 months, 3–5 months and 4–6 months, respectively. The first impact of the 2014 December MBI occurred in the Gulf of Finland in nine months as the arrival of the former Northern Baltic Proper deep layer water. Water renewal in the Fårö Deep occurred as a gravity current over the sill between Fårö and Gotland Deep. Deep layer water in the Northern Baltic Proper and the Gulf of Finland originated from the sub-halocline layer (110–120 m) of the Eastern Gotland Basin. The pre-condition for such mid-layer advection was a denser deep layer in the Gotland and Fårö Deep. Fresh oxygen, which arrived in the Gotland Deep in April 2015 and February 2016, was consumed in the near-bottom layer within 3–6 months. Since summer 2016, oxygenated waters occurred in the Gotland Deep in the layer from the halocline to 160 m depth. This oxygen did not reach the area further in the north, except a slight sign of ventilation of the Fårö Deep in February 2017. Thus, MBIs did not improve the oxygen conditions in the area north of the Gotland Deep and oxygen conditions rather worsened in the Northern Baltic Proper and the Gulf of Finland.